(untitled) (Acta Scientiarum. Health Sciences, 2025)
Acute herpetic gingivostomatitis (AHGS) is the oral manifestation of HVS-1 primary infection. Despite being a self-limiting infection, AHGS can progress to severe complications. Dentists should be prepared to correctly diagnose and treat the disease. Therefore, the purpose of this study is to assess knowledge, attitude, and practice (KAP) of dentists regarding acute herpetic gingivostomatitis (AHGS) among children. A cross-sectional and descriptive study was carried out through a KAP Survey of 416 Brazilian dentists. Descriptive analyzes with absolute and relative frequencies were performed and possible associations between socio-demographic variables with the KAP questions were investigated using Chi-square and Fisher’s exact tests (significance level 5%). Results revealed high knowledge scores among 68% of the dentists. The worst knowledge scores were found for AHGS complications. High scores were only associated with degree of education (p<0.005). For the treatment of AHGS, the responses were variable and signaled possible overtreatment in practice. Therapeutic possibilities beyond acyclovir are still lacking. This study highlights the importance of providing continuous education and integrating the practice of oral pathology into the practice of dentistry. It can help to increase knowledge, avoid overtreatment, and stimulate decision-making by the dentist in cases of complications.